Deoxyshikonin Inhibits Viability and Glycolysis by Suppressing the Akt/mTOR Pathway in Acute Myeloid Leukemia Cells - Wu, Huijuan; Zhao, Hongmian; Chen, Li (Frontiers in Oncology, 2020)
Deoxyshikonin was reported to exhibit anti-tumor effect in colorectal cancer. However, no studies are available to illustrate the effect of deoxyshikonin on acute myeloid leukemia (AML). Effects of deoxyshikonin on the viability, apoptosis, caspase-3/7 activity, and cytochrome (Cyt) C expression were evaluated by CCK-8, flow cytometry analysis, caspase-3/7 activity assay, and western blot analysis, respectively. Glucose consumption and lactate production were measured to determine glycolysis level. The expression of pyruvate kinase M2 (PKM2) was detected by qRT-PCR and western blot analysis. Results showed that deoxyshikonin inhibited cell viability and increased the apoptotic rate, caspase-3/7 activity, and Cyt C protein level in AML cells in a dose-dependent manner. Additionally, deoxyshikonin concentration-dependently decreased glucose consumption, lactate production, and PKM2 expression in AML cells. Deoxyshikonin inactivated the protein kinase B (Akt)/mammalian target of rapamycin (mTOR) pathway. Activation of the Akt/mTOR pathway reversed the effects of deoxyshikonin on viability, apoptosis and glycolysis in AML cells. In conclusion, deoxyshikonin dampened viability and glycolysis of AML cells by suppressing PKM2 via inactivation of the Akt/mTOR signaling.